Mastery-Based Testing in Undergraduate Mathematics Courses. Issue 5 (28th May 2019) - B. Collins, J.; Harsy, Amanda; Hart, Jarod; Anne Haymaker, Katie; (Armstrong) Hoofnagle, Alyssa Marie; Kuyper Janssen, Mike; Stewart Kelly, Jessica; Tyler Mohr,, Austin; OShaughnessy, Jessica
Abstract: Mastery-based testing is an assessment scheme that challenges students to provide complete solutions to problems derived from clear course concepts. Students are allowed multiple attempts to demonstrate mastery, which helps create a classroom environment where students value persistence toward thorough understanding. In this paper, we describe in detail the benefits and implementation of mastery-based testing in college mathematics courses. We also summarize student response data that show positive reactions to this testing method.